2017
DOI: 10.1016/j.fsi.2016.11.040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed-based vaccination on tilapia farm endemic for streptococcosis

Abstract: A tilapia farm experiencing endemic streptococcosis was selected to study the effect of vaccination with a feed-based vaccine on naturally ocurring streptococcosis. A total of 9000 red tilapia, Oreochromis niloticus × Oreochromis mossambicus of 100 ± 20 g were divided into 9 cages. Fish of Group 1 in cages 1, 2 and 3 were not vaccinated. Group 2 in cages 4, 5 and 6 were vaccinated on days 0 and 14 (single booster) while Group 3 in cages 7, 8 and 9 were vaccinated on days 0, 14 and 42 (double booster). Vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
2
23
1
Order By: Relevance
“…Ismail et al. (, ) also showed that antibody titers and host survival (75.1%) of a double booster vaccination were significantly higher than those of a single vaccination against S. agalactiae in tilapia. Thus, antigen dose should be optimized to correspond with vaccine protection in immunized fish (Dubey et al.…”
Section: Factors Influencing Vaccine Efficacymentioning
confidence: 94%
See 1 more Smart Citation
“…Ismail et al. (, ) also showed that antibody titers and host survival (75.1%) of a double booster vaccination were significantly higher than those of a single vaccination against S. agalactiae in tilapia. Thus, antigen dose should be optimized to correspond with vaccine protection in immunized fish (Dubey et al.…”
Section: Factors Influencing Vaccine Efficacymentioning
confidence: 94%
“…Despite the fact that the tilapia industry has improved rapidly, it also faces huge challenges from different catastrophic bacterial and viral diseases (Ismail et al. , ). Among these infectious bacterial diseases, the most common are motile aeromonad septicemia (MAS) (Cruz‐Papa et al.…”
mentioning
confidence: 99%
“…This disease is characterized by loss of appetite, exophthalmia, eye haemorrhage, corneal opacity, distended abdomen, curvature of the spinal cord, abnormal swimming behaviour and severe inflammation (Asencios et al., ; Iregui, Comas, Vásquez, & Verján, ; Van Doan et al., ), causing high mortality and severe economic losses in species such as red tilapia ( Oreochromis sp.) (Isiaku et al., ), Nile tilapia ( Oreochromis niloticus ) (Van Doan et al., ) and Mozambique tilapia ( Oreochromis mossambicus ) (Ismail et al., ). In the particular interest, the gills are considered one of the most affected tissues by S. agalactiae, causing severe histological alterations characterized by congestion, haemorrhage and proliferation on inflammatory cells, that contributes to high mortality (Su et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of selective and intensive culture, tilapias have been reported to be severely infected by pathogenic Streptococcus, and the resultant streptococcosis is one of the key fish diseases with high morbidity and mortality rates (Amal & Zamrisaad, ; Shen, Ma, Liu, & Yue, ). It has been estimated globally that the economic losses caused by streptococcosis outbreaks were as high as ten billion dollars annually (Ismail et al, ). S. agalactiae and S. iniae were recently discovered as the two most frequently detected pathogenic bacteria that trigger streptococcosis with similar clinical signs in the infected tilapia.…”
mentioning
confidence: 99%
“…Streptococcosis reported in intensive aquaculture systems is a major disease of tilapia which is usually caused by S. agalactiae and S. iniae infections and results in high economic loss in the aquaculture industry (Amal & Zamrisaad, ; Ismail et al, ; Najiah, Wei, & Nadirah, ). S. agalactiae and S. iniae have been reported to be present in the same geographic area and even on the same farm; therefore, in many cases, proper detection techniques are required to diagnose S. agalactiae and S. iniae simultaneously.…”
mentioning
confidence: 99%